A Boy with Chronic Active EBV Infection Presented as Mosquito Bite Hypersensitivity Progressed to Fatal Hemophagocytic Lymphohistiocytosis due to NK Cell Neoplasm - Jin Ah Lee; Seung Beom Han; Nack Gyun Chung; Jin Han Kang; Myungshin Kim; Dae Chul Jeong (The Korean Society of Pediatric Hematology-Oncology, 2019)
Chronic active Epstein-Barr virus (CAEBV) infection is characterized by recurrent infectious mononucleosis (IM)-like symptoms and an unusual pattern of anti-EBV antibodies. We report a boy with CAEBV who progressed to aggressive hemophagocytic lymphohistiocytosis (HLH) with NK cell neoplasm. A 19-year-old adolescent boy was admitted with fever and a history of recurrent IM-like symptoms following mosquito bites since the age of 6 years. His condition was diagnosed as CAEBV with atypical lymphocytosis and an unusual pattern of anti-EBV antibodies. His symptoms subsided during treatment with steroids and cyclosporine, although the EBV genome load kept increasing for several years. He was re-admitted after follow-up loss for 8 years, and his clinical and laboratory findings confirmed HLH and high titer of the EBV genome. Bone marrow analysis with flow cytometry showed hemophagocytosis with compatible NK cell neoplasm. He rapidly progressed to pulmonary infection and expired soon after. We conclude that hematopoietic stem cell transplantation may be a potential therapeutic modality for treating CAEBV before serious EBV manifestations.